Switchable Adhesion of Micropillar Adhesive on Rough Surfaces. Issue 50 (14th November 2019) - Tan, Di; Wang, Xin; Liu, Quan; Shi, Kui; Yang, Baisong; Liu, Sheng; Wu, Zhong‐Shuai; Xue, Longjian
Abstract: Switchable structured adhesion on rough surfaces is highly desired for a wide range of applications. Combing the advantages of gecko seta and creeper root, a switchable fibrillar adhesive composed of polyurethane (PU) as the backing layer and graphene/shape memory polymer (GSMP) as the pillar array is developed. The photothermal effect of graphene (under UV irradiation) changes GSMP micropillars into the viscoelastic state, allowing easy and intimate contact on surfaces with a wide range of roughness. By controlling the phase state of GSMP via UV irradiation during detachment, the GSMP micropillar array can be switched between the robust‐adhesion state (UV off) and low‐adhesion state (UV on). The state of GSMP micropillars determines the adhesion force capacity and the stress distribution at the detaching interface, and therefore the adhesion performance. The PU‐GSMP adhesive achieves large adhesion strength (278 kPa), high switching ratio (29), and fast switching (10 s) at the same time. The results suggest a design principle for bioinspired structured adhesives, especially for reversible adhesion on surfaces with a wide range of roughness. Abstract : The phase change of micropillar arrays between viscoelastic and glassy states switches the adhesion force capacity and the stress distribution at the detaching interface, and therefore the adhesion performance on surfaces with a wide range of roughness. The adhesive proposed can achieve large adhesion strength (278 kPa), high switching ratio (29), and fast switching (10 s) at the same time.